(Re)producing orientalism - Yizhou Xu (Eludamos)
Through the case study of the mobile title Game of Sultans, this article examines the proliferation of iterative and copycat games through the practice of reskins in the mobile game industry. Based on year-long autoethnographic fieldwork working in a Chinese mobile game company, I provide an on-the-ground perspective of how Orientalist representations in reskinned games are instrumentalized through the roles of “cultural brokers” and the work of localization for Western markets. By taking a theoretical and technological understanding of reskins, I argue that reskinned games, as a form of industrial mimicry, while an important aspect of standardized game production, can also serve as means of subversion against seemingly totalizing control of the US-dominated app economy. This article addresses the dearth of studies in theorizing the industry practice of game reskins beyond just a monetization tool but also its extractive labor process within the global app empire.